2023
DOI: 10.3389/fimmu.2023.1086078
|View full text |Cite
|
Sign up to set email alerts
|

Targeted modulation of gut microbiota by traditional Chinese medicine and natural products for liver disease therapy

Abstract: The gut microbiota not only constitutes intestinal microenvironment homeostasis and human health but also exerts indispensable roles in the occurrence and progression of multiple liver diseases, including alcohol-related liver disease, nonalcoholic fatty liver disease, autoimmune liver disease and liver cancer. Given the therapeutic status of these diseases, their prevention and early therapy are crucial, and the detailed mechanism of gut microbiota in liver disease urgently needs to be explored. Meanwhile, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…Compared to the typical structures observed in healthy individuals, study has revealed modified intestinal tight junctions and inflammatory infiltrates within the lamina propria of AIH patients. These modifications result in damage to the intestinal mucosa and elevated levels of endotoxins in the bloodstream, thereby triggering the immune tolerance impairment mechanism and causing liver injury (Kharrazian et al, 2023;Zhang et al, 2023b;Zhu et al, 2023). Under normal physiological conditions, anaerobic/aerobic bacteria in the intestinal microbiota maintain a dynamic balance and participate in physiological processes, and the disruption of this balance also can lead to intestinal barrier damage and bacterial translocation across the intestinal barrier to other organs, resulting in inflammation, immune disorders, and various other adverse effects (Lin et al, 2015).…”
Section: Gut Microbialmentioning
confidence: 99%
“…Compared to the typical structures observed in healthy individuals, study has revealed modified intestinal tight junctions and inflammatory infiltrates within the lamina propria of AIH patients. These modifications result in damage to the intestinal mucosa and elevated levels of endotoxins in the bloodstream, thereby triggering the immune tolerance impairment mechanism and causing liver injury (Kharrazian et al, 2023;Zhang et al, 2023b;Zhu et al, 2023). Under normal physiological conditions, anaerobic/aerobic bacteria in the intestinal microbiota maintain a dynamic balance and participate in physiological processes, and the disruption of this balance also can lead to intestinal barrier damage and bacterial translocation across the intestinal barrier to other organs, resulting in inflammation, immune disorders, and various other adverse effects (Lin et al, 2015).…”
Section: Gut Microbialmentioning
confidence: 99%
“…These interactions have two primary effects: (1) Enhancing effects: TCM modulates gut microbiota composition and metabolism, improving host health while the microbiota enhances TCM bioavailability. (2) Inhibitory effects: Some TCM constituents can weaken gut microbiota metabolic functions, and certain microbes may inhibit TCM absorption and metabolism ( Zhu et al., 2023 ). A recent review revealed that numerous natural molecules (e.g., apigenin, berberine, and quercetin) and plant extracts can effectively alleviate experimental autoimmune myocarditis.…”
Section: Current Strategies For Modulating Gut Microbiotamentioning
confidence: 99%
“…These pills are commonly used to treat chronic gastroenteritis, indigestion, loss of appetite, vomiting, and diarrhea [ 13 ]. The metabolites produced by different feed additives significantly impact the structure of the intestinal flora and play a crucial role in stress-induced diarrhea in weaned piglets [ 14 ]. The interaction between the metabolism of the intestinal flora and the nutrient metabolism of the host contributes to the maintenance of the intestinal tract and the overall health of the host [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolites produced by different feed additives significantly impact the structure of the intestinal flora and play a crucial role in stress-induced diarrhea in weaned piglets [ 14 ]. The interaction between the metabolism of the intestinal flora and the nutrient metabolism of the host contributes to the maintenance of the intestinal tract and the overall health of the host [ 14 ]. Metabolites provide detailed information about the biological endpoints as downstream components of gene regulatory networks and protein interaction networks [ 15 ].…”
Section: Introductionmentioning
confidence: 99%